Innovative Approaches to the Treatment of Fractures of the Proximal Femur: From Traditional Techniques to Modern Technologies (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article analyzes modern approaches to the treatment of fractures of the proximal femur, focusing on innovative methods and technologies that can significantly improve the results of treatment and the quality of life of patients. The article discusses the latest achievements in the field of surgical intervention, pharmacotherapy and rehabilitation.